2018
DOI: 10.1021/acs.chemmater.8b02765
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Proton Conductivity in Nonporous Metal–Organic Frameworks: The Role of Framework Proton Density and Humidity

Abstract: Owing to their inherent pore structure, porous metal−organic frameworks (MOFs) can undergo postsynthetic modification, such as loading extra-framework proton carriers. However, strategies for improving the proton conductivity for nonporous MOFs are largely lacking, although increasing numbers of nonporous MOFs exhibit promising proton conductivities. Often, high humidity is required for nonporous MOFs to achieve high conductivities, but to date no clear mechanisms have been experimentally identified. Here we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…Another strategy for stabilizing the proton transfer pathway is to exploit more acidic hydroxyl groups on the framework surface. Pili et al (2018), [67] ], (H 4 L 2 = benzene-1,4-diphosphonic acid; M=La, Ce, Nd, Sm, Gd, Ho) that were characterized with 2 H NMR and NS. MFM-555(Ho) has the highest conductivity value (1 0 À 4 S cm À 1 ), among these MOFs and its proton-conduction mechanism was investigated.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
See 3 more Smart Citations
“…Another strategy for stabilizing the proton transfer pathway is to exploit more acidic hydroxyl groups on the framework surface. Pili et al (2018), [67] ], (H 4 L 2 = benzene-1,4-diphosphonic acid; M=La, Ce, Nd, Sm, Gd, Ho) that were characterized with 2 H NMR and NS. MFM-555(Ho) has the highest conductivity value (1 0 À 4 S cm À 1 ), among these MOFs and its proton-conduction mechanism was investigated.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Currently, the application of the INS to probe the proton vibrational states in MOF systems is scarce. However, in a recent study by Pili et al in 2018, [67] INS was applied to probe the presence of the hydroxyl groups in the metal phosphonate non-porous MOF MFM-555(Ho). The INS spectrum showed the well-resolved peaks that were assigned to the vibrational modes of the phosphonate moiety, by means of the DFT calculations: The OÀ PÀ OÀ H wagging and PÀ OÀ H stretching modes were assigned to the peaks at 203 and 208 cm À 1 , respectively, and the PÀ O stretching modes were assigned to the peaks at 878 and 979 cm À 1 .…”
Section: Quasi Elastic Neutrons Scattering (Qens)mentioning
confidence: 99%
See 2 more Smart Citations
“…In most of the studies, the Grotthuss mechanism is suggested for many MOFs basing on the activation energy values. Recently, deuterium NMR spectroscopy and quasielastic neutron scattering (QENS) techniques have been used to get some insight into proton dynamics …”
Section: Proton Conductivity In Mofs For Fuel Cell Applicationmentioning
confidence: 99%